Influence of a plasma swirl motion on fine magnetic concentrations in the solar photosphere - Vargas Domínguez, Santiago; Palacios, Judith; Balmaceda, Laura; Domingo, Vicente (TECCIENCIA, 2016)
High-resolution observations from ground-based (Solar Swedish Telescope) and space-borne (Hinode) solar telescopes acquired data with various filters, obtaining images of a quiet Sun region populated with small-scale magnetic elements. The region is also characterized by the presence of photospheric swirl convective plasma structures. This work abridges the results of different analysis applied over time series of images to follow the evolution of magnetic features aiming to establish the influence of the plasma vortices on their motions.